Estimating the Effect of Common Currencies on Trade: The Case Study of EU and Turkey - Naib Alakbarov (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
Here is estimated the effect of monetary union and the exchange rate volatility on trade. First of all, Frankel and Rose (1997, 1998) have developed the idea that the suitability of European countries for the EMU cannot be judged on the basis of historical data. I use an augmented gravity model to estimate the effects of currency unions and exchange rate volatility on trade. The model is “augmented” in that the standard gravity model only includes income and distance variables. The estimated results show that two countries that use the same currency trade more, but it can be seen that the currency union effect of trade is not large. These findings are similar to those in Nardis and Vicarelli (2003). That is, they are not as large as those found in Rose (2000) and Glick and Rose (2002). The effect of the variable of ECU is also positive und significant. These findings are similar to those in Berger and Nitsch (2005), which claim that the potential trade-creating affects of the EMU must be viewed and analyzed in the proper historical perspective.
Keywords: 330; Currency Areas; Lucas Critique; Trade Integration; gravity equation